A Challenging Case of the Forgotten Abdominal Tuberculosis in the Developed World. Issue 3 (12th August 2021) - Henen, Sara; Denton, Christine; Miller, Aaron; Pappa, Helen
Abstract : Differentiating abdominal tuberculosis (TB) from Crohn's disease (CD) despite the rarity of the condition remains vital to avoid catastrophic consequences of disseminated miliary TB as a result of mistakenly starting an immunosuppressive medication. We highlight a challenging pediatric abdominal TB case of a 5-year-old male that presented with failure to thrive, ascites, and diarrhea. Our case aims to shed light on a forgotten disease in our developed world by highlighting subtle clinical, endoscopic, and histologic features. Findings of caseating necrosis on biopsy, positive smear for acid-fast bacillus (AFB), AFB culture, and necrotic lymph node on imaging are diagnostic of TB but are rarely present. Clinicians should be vigilant in screening pediatric patients with elusive symptoms, history, and exam. TB should be suspected, and one should not shy away from empirical antituberculous treatment as it could be the only way of establishing the diagnosis.